Analisis Pengaruh Kualitas Website Terhadap Kepuasan Pengguna Berdasarkan Metode WebQual 4.0 Pada Website Kemahasiswaan Institut Bisnis Dan Informatika Stikom Surabaya - Hadi, Andhika Pratama; Sulistiowati, Sulistiowati; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Institute of business and Informatics Stikom Surabaya founded a Department named a student center has a duty to develop the human resources (HR), in line with the development of Student Affairs section Stikom Surabaya, making a Website i.e. kemahasiswaan.stikom.edu where this website was created with the aim to make it easier for students to obtain information about activities that can help students increase Softskill.In this research, conducted an analysis of the influence of the quality of Student Affairs website Stikom Surabaya against user satisfaction based on the perception of the end user that is using webqual 4.0. Data collection is done by giving a questionnaire online and offline. Furthermore the results of the questionnaire will be analyzed based on indicators of webqual. Results of questionnaire data and then do test the validity, reliability, test the assumption of Linear regression test as a condition.Based on this research resulted in the conclusion that the usability quality and the interaction quality is positive and significant effect against user satisfaction. While the information quality does not have a positive influence and significantly to the user satisfaction.